Managing Adhesive Small Bowel Obstruction with Water-Soluble Contrast Should Be Protocolized: A Retrospective Analysis - Köstenbauer, Jakob K. (The Surgery Journal, 2018)
Aim Current literature emphasizes the effectiveness of computed tomography (CT) and water-soluble contrast agent, Gastrografin, in the investigation of adhesive small bowel obstruction (ASBO). As there is no management protocol for ASBO at our institution, the aim of this study was to determine the effect of imaging methods—CT, Gastrografin challenge (GC), or plain-film X-ray—on patient outcomes in a clinical setting.Methods All 163 emergency presentations of ASBO during the study period between December 2010 and September 2012 were collected retrospectively. Cases were divided into three groups: CT with oral contrast, GC, or plain-film X-ray only. The primary outcome was time to theater.Results Patients investigated with X-ray only were significantly less likely to require surgery (6% in plain-film X-ray vs. 35% and 20% in CT and GC, respectively; p = 0.003). In cases requiring surgery, GC was associated with a 24-hour longer time to imaging than CT (p < 0.001). The time to theater was 71:25 hours for GC versus 46:39 for CT (p = 0.039). There was no significant difference in bowel resection or complication rates.Conclusion Patients undergoing water-soluble contrast studies were subjected to unnecessary delays in their clinical course. These delays are costly and avoidable. The development and implementation of an evidence-based protocol for the management of small bowel obstruction is strongly recommended. The lack of a protocol likely caused significant delays in Gastrografin administration, reducing its known benefits for clinical decision-making and length of stay.
Keywords: Gastrografin; water-soluble contrast agents; adhesions; small bowel obstruction; management protocol; computed tomography